Managerial Accounting (11th Edition) - C.Brewer Peter (McGraw -Hill, 2004)
As the long-time best-seller, Garrison has helped guide close to 2 million students through the challenging waters of managerial accounting since it was first published. It identifies the three functions managers must perform within their organizations-plan operations, control activities, and make decisions-and explains what accounting information is necessary for these functions, how to collect it, and how to interpret it. To achieve this, Managerial Accounting, 11/E, focuses, now as in the past, on three qualities: Relevance: Every effort is made to help students relate the concepts in this book to the decisions made by working managers. With insightful chapter openers, the popular Managerial Accounting in Action segments within the chapters, and stimulating end-of-chapter exercises, a student reading Garrison should never have to ask "Why am I learning this?" Balance: There’s more than one type of business, and so Garrison covers a variety of business models, including not-for-profit, retail, service, and wholesale organizations as well as manufacturing. In the eleventh edition, service company examples are highlighted with icons in the margins of the text. Clarity: Generations of students have praised Garrison for the friendliness and readability of its writing, but that’s just the beginning. Technical discussions have been simplified, material has been reordered, and the entire book carefully retuned to make teaching-and learning-from Garrison as easy as it can be. In addition, the supplements package is written by Garrison, Noreen, and Brewer, ensuring that students and professors will work with clear, well-written supplements that employ consistent terminology.